2017
DOI: 10.1590/0001-3765201720160177
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan overloading activates brain regions involved with cognition, mood and anxiety

Abstract: Tryptophan is the only precursor of serotonin and mediates serotonergic activity in the brain. Previous studies have shown that the administration of tryptophan or tryptophan depletion significantly alters cognition, mood and anxiety. Nevertheless, the neurobiological alterations that follow these changes have not yet been fully investigated. The aim of this study was to verify the effects of a tryptophan-enriched diet on immunoreactivity to Fos-protein in the rat brain. Sixteen male Wistar rats were distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…[28] demonstrated that a tryptophan-abundant diet led to greater levels of Fos-immunoreactivity (Fos-ir), and therefore brain activity, in areas of the brain responsible for mediating anxiety: the PFC, nucleus accumbens, paraventricular hypothalamus, arcuate and ventromedial hypothalamus, dorsolateral and dorsomedial periaqueductal grey, DRN, and median raphe nucleus (MRN). Hsiao et al…”
mentioning
confidence: 99%
“…[28] demonstrated that a tryptophan-abundant diet led to greater levels of Fos-immunoreactivity (Fos-ir), and therefore brain activity, in areas of the brain responsible for mediating anxiety: the PFC, nucleus accumbens, paraventricular hypothalamus, arcuate and ventromedial hypothalamus, dorsolateral and dorsomedial periaqueductal grey, DRN, and median raphe nucleus (MRN). Hsiao et al…”
mentioning
confidence: 99%
“…Hypothalamus has the ability to produce a hormone that can control appetite, namely serotonin. Tryptophan is an important element needed by the body in the balance of serotonin, melatonin and other hormones that are important in the body's metabolism (Silva et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Такая выраженная поло-жительная динамика продуктивности мышления по сравнению с речью и слухоречевой памятью может объясняться особенностями изучаемых видов мышления -наглядно-действенного и на-глядно-образного, в которых ведущими являют-ся зрительный и пространственный компонен-ты [16]. Через них, вероятно, и реализуется преимущественно фармакологический ýффект L-триптофана, что согласуется с проведенными ранее исследованиями [17].…”
Section: Discussionunclassified